Fusobacterium nucleatum: An unusual cause of subdural empyema. Issue 12 (December 2016) - Yocum, Denise
Abstract : ABSTRACT: This article describes an uncommon presentation of a subdural empyema in a young man. Because the patient's initial presentation consisted of nonspecific abdominal complaints, subdural empyema was not initially considered. However, a thorough medical history, including recent travel history, and appropriate multidisciplinary consultation, were key to reaching the correct diagnosis.